Indian economy - Fernando, A. C., 1940- (Pearson India Education Services, 2018)
This book on the Indian economy is an exhaustive text for studying and understanding the world's third largest economy. Written in a simple and lucid language, the book presents the subject matter in a manner where a reader will be able to easily move from elementary to complex concepts. Special attention has also been paid to discuss the latest developments, policies, and problems related to the Indian economy. The content coverage has been designed to help students pursuing graduate and postgraduate courses in commerce, economics, and management as well as those pursuing professional programmes such as chartered accountancy, company secretary, and cost and works accountancy.